Correlation of Fasting Blood Glucose With IL-6 Levels in Type-2 Diabetes Mellitus Ethnic Minangkabau - Elsa Yuniarti; Syam Syamsurizal; Yuni Ahda; Puja Delfi Sonata (UNIVERSITAS NEGERI PADANG, 2018)
Diabetes Mellitus (DM) Type 2 is a metabolic disorder disease characterized by an increase in blood sugar (hyperglycemia) due to decreased insulin secretion by pancreatic beta cells or intrusion of insulin function. Hyperglycemia tends to cause oxidative stress where free radical formation exceeds the body's antioxidant defense system resulting in microvascular and macrovascular disorders. Some ethnic groups have a tendency to develop type 2 diabetes mellitus because of differences in diet, lifestyle and physical activity. In addition, ethnicity is also suspected to affect the levels of IL-6. This study aims to determine the correlation of fasting blood sugar levels with IL-6 levels in type 2 diabetes mellitus ethnic Minangkabau. This research is cross sectional comparative research design. The subjects of two groups: DM type 2 and control group (non-DM) who went to the Polyclinic of State University of Padang, Minangkabau ethnic and each consisted of 35 people. Blood glucometer examination with blood sample and IL-6 measurement using ELISA technique with serum sample. Fasting blood sugar levels in patients with Type 2 DM Minangkabau ethnic average 286.2 ± 80.46 mg / dl while non DM 101.26 ± 9.70 mg / dl. Mean IL-6 levels in type 2 DM patients were 16.23 ± 30.12 pg / ml while non-DM of 3.41 ± 1.91 pg / ml was an increase of about 4.7 in patients with type 2 DM Compared to non-ethnic minority of Minangkabau with p value <0,05. The result of research that have been done there is a positive correlation between fasting blood sugar level with IL -6 in patients with Type 2 DM Minangkabau ethnic with r value = 0,44 at p <0.05 which means interpretation of medium correlation strength. Keywords: Type 2 DM, IL-6, ethnic Minangkabau